Provoking Active Learning among Student Teachers in Distance Education through a Dialogical Online Tutorial Approach - Titi Chandrawati; David Kaufman; Charles Scott (Yayasan Adra Karima Hubbi, 2026)
Background. Distance education environments often face challenges in fostering active learning because online interactions can easily become teacher-centered, leading students to act as passive recipients of information. A dialogical learning approach is considered a potential strategy to promote participation and reduce passive learning patterns in online tutorials. Purpose. This study aims to analyze the use of a dialogical approach in provoking active learning among student teachers participating in online tutorials at Universitas Terbuka (UT). Method. This research employed a qualitative case study design to explore the implementation of a dialogue-based learning approach in an online tutorial. The participants consisted of nine student teachers enrolled in the Early Childhood Education program, all of whom were practicing kindergarten teachers, along with one online tutor facilitating the tutorial. Data were collected through observations of online tutorial interactions and participants’ reflections on their learning experiences. Results. The findings indicate that the dialogical approach successfully encouraged student teachers to become more active learners during the online tutorials. Through structured dialogue, participants were able to exchange ideas, share professional experiences, and collaboratively construct knowledge. The dialogical interaction also reduced the tendency toward the banking concept of education by fostering reciprocal communication between tutor and students. Conclusion. The implementation of a dialogical learning approach in distance education can enhance student participation and support meaningful learning experiences. This approach provides an effective strategy for promoting active engagement among student teachers in online learning environments.